Aspek Hukum Perjanjian Pemberian Bantuan Pinjaman Modal Antara Badan Usaha Mlik Negara Kepada Usaha Mikro Kecil - Rahdiansyah Rahdiansyah (UIR Law Review, 2018)
State-Owned Enterprises as the implementer of partnership programs, has an obligation to provide business capital loan assistance to small businesses in accordance with the decision of the Minister of State-Owned Enterprises and State-Owned Enterprises No. 236 / MBU / 2003 on partnership programs State-Owned Enterprises with Small Business and Community Development Program. The provision of grant of business capital loan to small business which is better known as this partnership program has a goal to increase the capability of small scale business through the utilization of fund from the profit share of State Owned Enterprises in this program. BUMN Pembina is prohibited to provide business loan small businesses that have become partners of other State-Owned Enterprises (BUMN).